Analysis of the In Vivo Transcriptome of Bordetella pertussis during Infection of Mice - Ting Y. Wong (American Society for Microbiology, 2019)
ABSTRACT Bordetella pertussis causes the disease whooping cough through coordinated control of virulence factors by the Bordetella virulence gene system. Microarrays and, more recently, RNA sequencing (RNA-seq) have been used to describe in vitro gene expression profiles of B. pertussis and other pathogens. In previous studies, we have analyzed the in vitro gene expression profiles of B. pertussis, and we hypothesize that the infection transcriptome profile in vivo is significantly different from that under laboratory growth conditions. To study the infection transcriptome of B. pertussis, we developed a simple filtration technique for isolation of bacteria from infected lungs. The work flow involves filtering the bacteria out of the lung homogenate using a 5-μm-pore-size syringe filter. The captured bacteria are then lysed to isolate RNA for Illumina library preparation and RNA-seq analysis. Upon comparing the in vitro and in vivo gene expression profiles, we identified 351 and 255 genes as activated and repressed, respectively, during murine lung infection. As expected, numerous genes associated with virulent-phase growth were activated in the murine host, including pertussis toxin (PT), the PT secretion apparatus, and the type III secretion system. A significant number of genes encoding iron acquisition and heme uptake proteins were highly expressed during infection, supporting iron acquisition as critical for B. pertussis survival in vivo. Numerous metabolic genes were repressed during infection. Overall, these data shed light on the gene expression profile of B. pertussis during infection, and this method will facilitate efforts to understand how this pathogen causes infection. IMPORTANCE In vitro growth conditions for bacteria do not fully recapitulate the host environment. RNA sequencing transcriptome analysis allows for the characterization of the infection gene expression profiles of pathogens in complex environments. Isolation of the pathogen from infected tissues is critical because of the large amounts of host RNA present in crude lysates of infected organs. A filtration method was developed that enabled enrichment of the pathogen RNA for RNA-seq analysis. The resulting data describe the “infection transcriptome” of B. pertussis in the murine lung. This strategy can be utilized for pathogens in other hosts and, thus, expand our knowledge of what bacteria express during infection.